Perceptions of open‐source software developers on collaborations: An interview and survey study. Issue 5 (24th October 2021) - Constantino, Kattiana; Souza, Mauricio; Zhou, Shurui; Figueiredo, Eduardo; Kästner, Christian
Abstract: With the emergence of social coding platforms, collaboration has become a key and dynamic aspect to the success of software projects. In such platforms, developers have to collaborate and deal with issues of collaboration in open‐source software development. Although collaboration is challenging, collaborative development produces better software systems than any developer could produce alone. Several approaches have investigated collaboration challenges, for instance, by proposing or evaluating models and tools to support collaborative work. Despite the undeniable importance of the existing efforts in this direction, there are few works on collaboration from perspectives of developers. In this work, we aim to investigate the perceptions of open‐source software developers on collaborations, such as motivations, techniques, and tools to support global, productive, and collaborative development. Following an ad hoc literature review, an exploratory interview study with 12 open‐source software developers from GitHub, our novel approach for this problem also relies on an extensive survey with 121 developers to confirm or refute the interview results. We found different collaborative contributions, such as managing change requests. Besides, we observed that most collaborators prefer to collaborate with the core team instead of their peers. We also found that most collaboration happens in software development (60%) and maintenance (47%) tasks. Furthermore, despite personal preferences to work independently, developers still consider collaborating with others in specific task categories, for instance, software development. Finally, developers also expressed the importance of the social coding platforms, such as GitHub, to support maintainers, and contributors in making decisions and developing tasks of the projects. Therefore, these findings may help project leaders optimize the collaborations among developers and reduce entry barriers. Moreover, these findings may support the project collaborators in understanding the collaboration process and engaging others in the project. Abstract : The paper investigates the perceptions of open‐source software developers on collaborations. Following an ad hoc literature review and an exploratory interview study with 12 developers, our novel approach also relies on an extensive survey with 121 developers. We observed that most collaborators prefer to collaborate with the core team instead of their peers. We also found that most collaboration happens in software development (60%). Finally, developers expressed the importance of the social coding platforms, such as GitHub, to support collaborators.